The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1021/bi00105a010
|View full text |Cite
|
Sign up to set email alerts
|

Proton linkage of complex formation between cytochrome c and cytochrome b5: electrostatic consequences of protein-protein interactions

Abstract: Two potentiometric methods have been used to study the pH-dependent changes in proton binding that accompany complex formation between cytochrome c and cytochrome b5. With one method, the number of protons bound or released upon addition of one cytochrome to the other has been measured as a function of pH. The results from these studies are correlated with the complexation-induced difference titration curve calculated from the titration curves of the preformed complex and of the individual proteins. Both metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 58 publications
1
36
0
Order By: Relevance
“…These data suggest that electrostatic forces are involved in complex formation and that as solvent is excluded from the protein-protein interface hydration forces are replaced by salt linkages (Rogers, Pochapsky & Sligar, 1988;Mauk, Barker & Mauk, 1991;Kornblatt, Kornblatt, Hoa & Mauk, 1993). Computer models of such complexes (Salemme, 1976;Poulos & Mauk, 1983;Wendoloski, Mathew, Weber & Salemme, 1987), together with mutagenic studies, have identified negatively charged groups on b5 which link with positively charged residues surrounding the heme pocket of its partners.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that electrostatic forces are involved in complex formation and that as solvent is excluded from the protein-protein interface hydration forces are replaced by salt linkages (Rogers, Pochapsky & Sligar, 1988;Mauk, Barker & Mauk, 1991;Kornblatt, Kornblatt, Hoa & Mauk, 1993). Computer models of such complexes (Salemme, 1976;Poulos & Mauk, 1983;Wendoloski, Mathew, Weber & Salemme, 1987), together with mutagenic studies, have identified negatively charged groups on b5 which link with positively charged residues surrounding the heme pocket of its partners.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of Mn 2Ï© ions to wild-type Mb and the variant was studied by monitoring the release of protons upon metal ion binding. Instrumentation (27), preparation of metal ion solutions (28), and data acquisition and analysis procedures (28,29) were reported previously. The dependence of peroxidase activity on pH was evaluated at 25°C between pH 5.0 and 8.0 with a mixed buffer system (5 mM Mes͞5 mM Mops͞5 mM TAPS͞95 mM NaCl) [ (32).…”
Section: Methodsmentioning
confidence: 99%
“…The change in proton binding that is associated with the binding of Zn 2+ , Co 2+ , Ni 2+ , Mn 2+ , Cu 2+ and Fe 3+ to apoFurC* (5.69-6.44 ”M) was studied at 25 ‱ C by the method of Laskowski and Finkenstadt [37] with a Radiometer ABU93 Triburet operated under computer control as described previously [38]. Difficulties related to oxidation of Fe 2+ by dissolved dioxygen prevented consideration of the binding of this species to FurC*.…”
Section: Potentiometric Titrationsmentioning
confidence: 99%